2013
DOI: 10.1038/bjc.2013.589
|View full text |Cite
|
Sign up to set email alerts
|

Changing presentation of prostate cancer in a UK population – 10 year trends in prostate cancer risk profiles in the East of England

Abstract: Background:Prostate cancer incidence is rising in the United Kingdom but there is little data on whether the disease profile is changing. To address this, we interrogated a regional cancer registry for temporal changes in presenting disease characteristics.Methods:Prostate cancers diagnosed from 2000 to 2010 in the Anglian Cancer Network (n=21 044) were analysed. Risk groups (localised disease) were assigned based on NICE criteria. Age standardised incidence rates (IRs) were compared between 2000–2005 and 2006… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 18 publications
5
29
0
Order By: Relevance
“…The age range at the time of diagnosis of PCa in our study is also commonly reported from West Africa where studies from Ghana [9], Nigeria [10] and Senegal [11] recorded a mean age of 65.4, 66.6 and 65 years respectively. The age of diagnosis of PCa in our study is also similar to those reported from the developed world particularly in Europe and North America [12,13]. However, the majority of PCa cases are diagnosed in patients who are asymptomatic in the developed world due to the widespread use of the Prostate Specific Antigen (PSA) blood test [12][13][14].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The age range at the time of diagnosis of PCa in our study is also commonly reported from West Africa where studies from Ghana [9], Nigeria [10] and Senegal [11] recorded a mean age of 65.4, 66.6 and 65 years respectively. The age of diagnosis of PCa in our study is also similar to those reported from the developed world particularly in Europe and North America [12,13]. However, the majority of PCa cases are diagnosed in patients who are asymptomatic in the developed world due to the widespread use of the Prostate Specific Antigen (PSA) blood test [12][13][14].…”
Section: Discussionsupporting
confidence: 85%
“…The age of diagnosis of PCa in our study is also similar to those reported from the developed world particularly in Europe and North America [12,13]. However, the majority of PCa cases are diagnosed in patients who are asymptomatic in the developed world due to the widespread use of the Prostate Specific Antigen (PSA) blood test [12][13][14]. 68.7% of PCa cases were diagnosed in the absence of symptoms in the study of Muller [12] from the USA.…”
Section: Discussionsupporting
confidence: 85%
“…There has, however, been a slight increase in the number of intermediate risk patients in cohort 2 due to a shift to Gleason grade 7 tumours. Interestingly, the median PSA values are very similar, suggesting the two groups are similarly matched and the increase in Gleason grade 7 may reflect a change in pathological interpretation of grade, as reported in other studies [8]. There is a distinction however between the two groups in terms of a significant reduction in the use of neoadjuvant hormones pre-implant and a decrease in the number of patients with a D90 <125 Gy, leading to an increase in the median D90 overall for cohort 2.…”
Section: Discussionsupporting
confidence: 77%
“…Others have suggested that outside issues, such as financial reimbursement, lack of physician skill proficiency in brachytherapy, as well as stage migration towards more intermediate and high grade disease, which may be less likely to include prostate brachytherapy, have played a role in this trend [6]. These issues have led to several provocative studies suggesting that prostate brachytherapy is on a steep decline.…”
Section: Purposementioning
confidence: 99%